Development and testing of hybrid fuzzy logic controller for car suspension system using magneto-rheological damper - Muhammad Mahbubur, Rashid; Nasrudin Abd, Rahim; Mohamed Azlan, Hussain; Faisal A., Mohamed; Mahmudur Azizur, Rahman (2008)
In this paper, the development of a novel semiactive suspension control of quarter car model using fuzzy logic based controller has been done. The proposed quarter car model can be described as a nonlinear two degrees of freedom system, which is subject to system disturbances from different road profiles. In order to implement the suspension system experimentally, the magneto rheological (MR) fluid has been used as adjustable damper. The MR damper is a control device that consists of a hydraulic cylinder filled with magnetically polarizable particles suspended in a liquid. The MR dampers rapidly dissipate vibration by absorbing energy. In this work, a proportional integral derivative, a fuzzy logic and hybrid controllers are used to control the semi-active car suspension system. Results show that both fuzzy logic and hybrid controllers are quite suitable to eliminate road disturbances to the suspension system considerably as compared to the conventional PID controller.